MEDIA, GENDER, AND INCLUSIVE ECONOMY: A PROSPECTIVE ANALYSIS OF KNOWLEDGE OF WOMEN’S ECONOMIC EMPOWERMENT (WEE) AMONGST MEDIA PRACTITIONERS IN NIGERIA - Nsude, Ifeyinwa; Karofi, Hassan Aliyu (EBSU Journal of Social Sciences and Humanities, 2024)
This study delves into the intricate intersection of media, gender, and inclusive economic development in Nigeria. Its dual objectives are to assess the level of knowledge among Nigerian media practitioners regarding women’s economic empowerment and to analyse the media’s portrayal of pertinent issues in this domain. Employing a mixed-methods approach, the study incorporated qualitative design (Focus Group Discussions) and quantitative design (media content analysis) to gain comprehensive insights. Twenty participants (journalists specializing in women’s affairs), were selected from prominent Nigerian media outlets. Discussions had during FGDs covered various aspects, including participants’ knowledge, reporting experiences, challenges, and opportunities related to women’s economic empowerment. Verbatim transcripts ensured data accuracy. Simultaneously, a systematic collection of newspaper articles from April to November 2022 formed the basis of the media content analysis. The study engaged a diverse selection of newspapers, guaranteeing a wide spectrum of perspectives. Rigorous trend analysis techniques identified significant patterns and trends in media coverage of Women’s Economic Empowerment (WEE). Thematic data analysis was applied to FGD transcripts to unveil recurring themes and insightful findings. The media content analysis, in contrast, focused on a systematic trend analysis of selected newspaper articles, emphasizing key aspects of WEE. The study’s findings highlight trends in WEE coverage, the roles of diverse stakeholders, and media perspectives in Nigeria. These insights underscore the need for sustained, consistent efforts in women’s economic empowerment. Financial institutions, international organizations, local NGOs, and philanthropists play pivotal roles, necessitating collaborative efforts to ensure the sustainability of initiatives. Moreover, the study underscores the crucial role of the media in advancing the visibility of women’s economic empowerment and suggests strategies for improved reporting and advocacy. The exclusion of women’s co-operatives in COVID-19 palliative distribution emphasizes the urgency of inclusive government strategies to address poverty and economic exclusion among women. This research offers valuable insights to inform data-driven decisions and enhance women’s economic empowerment in Nigeria.